Pengembangan Ekonomi Melalui Pendampingan UMKM dengan Pemanfaatan Potensi Lokal di Desa Mandiri Geneng - Jati, Jati; Jeane Talakua (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of Micro, Small, and Medium Enterprises in Geneng Village had experienced a derivation. However, it can be seen that currently the development of Micro, Small and Medium Enterprises is starting to improve again. The village government's policy has been quite effective in developing Micro, Small and Medium Enterprises in Geneng Village. Labor absorption has also been quite high, although there are some Micro and Small Medium Enterprises business owners who are just developing. This is also supported by new product innovations, packaging, and marketing methods that can increase selling value. A good product certainly starts with quality raw materials and proper processing during the production process. Not only varied product innovations, but also promotion through digital media. Currently, many Micro, Small and Medium Enterprises in Geneng Village have marketed products using social media as the fastest means of promotion in this modern era. The increase in income or turnover is supported by better financial records, so that the owner or manager of Micro, Small and Medium Enterprises can know the development of the business periodically. The hope of the Geneng Village Government is that Micro, Small and Medium Enterprises in Geneng Village can continue to grow and develop even better in the future and increasingly open up employment opportunities for the surrounding community.